2016
DOI: 10.1111/add.13453
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of illicit drug use disorders in Iran: prevalence, correlates, comorbidity and service utilization results from the Iranian Mental Health Survey

Abstract: Opioid use disorders are the most common type of drug use disorders in Iran, setting Iran apart from many other countries. Patterns of service use suggest a large unmet need for drug use disorder treatment in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
175
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 28 publications
10
175
1
Order By: Relevance
“…Similar studies have also shown that the pleasure of smoking cigarette and its effect on reducing anxiety were the most important factors that increased students' tendency towards smoking (19). In the same line, various studies have shown that psychological problems, such as anxiety and depression, were the most important factors in increasing the youth's tendency to use drugs (23). In order to prevent smoking tobacco including hookah, causes of stress and anxiety among students have to be evaluated and, at the same time, students have to be trained regarding the necessary skills to solve their psychological problems.…”
Section: Discussionmentioning
confidence: 78%
“…Similar studies have also shown that the pleasure of smoking cigarette and its effect on reducing anxiety were the most important factors that increased students' tendency towards smoking (19). In the same line, various studies have shown that psychological problems, such as anxiety and depression, were the most important factors in increasing the youth's tendency to use drugs (23). In order to prevent smoking tobacco including hookah, causes of stress and anxiety among students have to be evaluated and, at the same time, students have to be trained regarding the necessary skills to solve their psychological problems.…”
Section: Discussionmentioning
confidence: 78%
“…Opium use was the most frequently reported illicit drug. Overall, 40% of the interviewees with opioid dependence reported unmet drug treatment needs in the last 12 months (1).…”
Section: Introductionmentioning
confidence: 99%
“…Iran MHS indicated that out of 7 841 interviewees, only 2.0% reported drug treatment in the last 12 months; 13.9% reported using TCP (1). A study of 71 opioid-dependents on TCP was conducted in Tehran.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly because of opioids being the most common drug of use in the Islamic Republic of Iran (1) in comparison to most other countries where cannabis is the most commonly used drug (2). In the past 15 years, drug use, mainly injecting drug use has contributed significantly to infectious diseases like HIV infection and viral hepatitis (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%